FAMILY PATTERN AS KEY FACTOR OF PRIMARY SCHOOL CHIDREN ACADEMIC PERFOMANCE - Karabalina, A. A.; Maydangalieva, Zh. A.; Satygalieva, G. B.; Ahmetalina, G. A.; Mahammadli, Dashqin (Scientific Journal of Pedagogy and Economics, 2018)
Nowadays many families face problems caused by differences in their view of the parental and educational style of upbringing. The progress of the child at school is one of the essential criteria of its assessment. The relationship in the family where emotionally atmosphere is warm, the family where parents are respectful to the identity of the child is defined, recognizing his rights, accepting it as the personality – give the child the chance successfully to develop and be successful in the study. We used specific methods: Varga, Stolin Questionnaire of the parental attitude towards children, Schubert Test "Definition of school motivation," «School test of IQ development" (ShTUR), Phillips Test level of school anxiety. We divided participants (48 students) into two groups (Control and Experimental). According to the results of research EG showed a low level of school motivation of 33,3%, these children attended school reluctantly, preferred to skip classes. At lessons students often were engaged in the different activity. We found significant differences in the results of the IQ test between EG and CG. The problem of influence of the dominating type of the parental relation on the child gained particular relevance today. From a strategy of behavior which parents choose depends on emotional, motivational children development.